What to Do With the Psychopaths? Treatment Successes and Failures - Katrin Lieck (Faculty of Psychology, Universitas Surabaya, 2013)
The popular opinion about the treatment of psychopathy is that it is not very promising. The personality traits that define the psychopath seem to be not compatible with traditional psychotherapy. This article reviews outcome studies on the treatment of psychopaths to answer the question whether treatment of psychopaths has positive outcomes. This article also emphasizes the role of brain abnormalities in psychopaths that may lead to the conclusion that social deficits of psychopaths are a cause of brain damage and therefore not treatable at all. It appears that treatment is not at all useless for psychopaths. Rather, there has to be made more effort to tailor traditional treatment methods to the characteristics and needs of psychopaths. It also appears that treatment for adolescent psychopaths is more promising than that of adult psychopaths. Further it seems that the ‘dose’ of treatment determines the outcome: More treatment than ‘treatment as usual’ is needed to reduce violent recidivism in psychopaths. Pendapat yang populer tentang perawatan/pengobatan psikopati adalah bahwa hal tersebut tidak banyak menjanjikan. Sifat-sifat kepribadian yang menggambarkan psikopat tampaknya tidak sesuai dengan psikoterapi tradisional. Artikel ini mereview hasil studi perawatan psikopat untuk menjawab pertanyaan apakah pengobatan psikopat memberi hasil yang positif. Artikel ini juga menekankan peran abnormalitas otak pada psikopat yang mungkin membawa pada simpulan bahwa defisit sosial para psikopat menjadi penyebab kerusakan otak dan karenanya tak mungkin diobati. Tampaknya perawatan tidak sama sekali tak berguna bagi para psikopat. Sesungguhnya, perlu lebih diupayakan mengemas metode perawatan tradisional sesuai kebutuhan para psikopat masing-masing. Tampak juga bahwa perawatan psikopat remaja lebih menjanjikan daripada psikopat dewasa. Selanjutnya tampak bahwa ”dosis” pengobatan menentukan hasilnya. Lebih banyak pengobatan daripada ”perawatan seperti biasanya” diperlukan untuk mengurangi kekambuhan yang ganas pada psikopat.